2018
DOI: 10.3892/ijmm.2018.3623
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirtuin 1 in the pathogenesis of ocular disease (Review)

Abstract: Sirtuin (SIRT)1, a member of the SIRT family, is a highly conserved NAD+‑dependent histone deacetylase, which has a regulatory role in numerous physiological and pathological processes by removing acetyl groups from various proteins. SIRT1 controls the activity of numerous transcription factors and cofactors, which impacts the downstream gene expression, and eventually alleviates oxidative stress and associated damage. Numerous studies have revealed that dysfunction of SIRT1 is linked with ocular diseases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 95 publications
(113 reference statements)
1
30
0
1
Order By: Relevance
“…The role of SIRT1, an NAD + -dependent histone deacetylase, in the progress and protection of retinal degeneration has been reported in great details in several disease models [45,46]. Jaliffa, C et al found that the pathologic expression pattern of SIRT1 was correlated with initial retinal degeneration in rd10 mice [47].…”
Section: Discussionmentioning
confidence: 99%
“…The role of SIRT1, an NAD + -dependent histone deacetylase, in the progress and protection of retinal degeneration has been reported in great details in several disease models [45,46]. Jaliffa, C et al found that the pathologic expression pattern of SIRT1 was correlated with initial retinal degeneration in rd10 mice [47].…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong link between SIRT1 expression and the development of DR and PDR. In particular, hyperglycemia and diabetes cause the downregulation of SIRT1, thus resulting in inflammation, angiogenesis, an increase in oxidative stress, and vascular permeability, all of which are hallmarks of diabetic damage [71]. There is a functional link between HMGB1 and SIRT1 in the regulation of the diabetes-induced breakdown of the BRB.…”
Section: Hmgb1 and Drmentioning
confidence: 99%
“…Among them, SIRT1 is the most well studied. SIRT1 is a highly conserved NAD + -dependent histone deacetylase that mediates the antioxidative stress in psoriasis [23,24]. It was reported that SIRT1 could promote the differentiation of human keratinocytes [25] and inhibit keratinocyte proliferation [26].…”
Section: Ros Mainly Include Superoxide Anion (O 2 −mentioning
confidence: 99%